2013
DOI: 10.3189/2013jog12j148
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on physical and textural properties of Arctic first-year sea ice in the Amundsen Gulf, Canada, November 2007–June 2008 (IPY-CFL system study)

Abstract: We report sea-ice temperature and bulk salinity measurements as well as textural analysis from 33 first-year drift- and fast-ice stations sampled between November 2007 and June 2008 in the southern Beaufort Sea–Amundsen Gulf, Canadian Arctic, during the International Polar Year Circumpolar Flaw Lead (IPY-CFL) system study. We use this significant dataset to investigate the halo-thermodynamic evolution of sea ice from growth to melt. A strong desalination phase is observed over a small time window in the spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 85 publications
6
39
1
Order By: Relevance
“…It is noteworthy that we did not observe full-depth brine convection at the beginning of the warming phase, as found in natural ice covers by Carnat et al (2013) and Zhou et al (2013). This is likely to be a result of the temperature not being low enough at the ice surface to promote a strong brine salinity gradient (a requirement for full-depth brine convection).…”
Section: Physical Imprints On Nutrient Incorporationsupporting
confidence: 55%
“…It is noteworthy that we did not observe full-depth brine convection at the beginning of the warming phase, as found in natural ice covers by Carnat et al (2013) and Zhou et al (2013). This is likely to be a result of the temperature not being low enough at the ice surface to promote a strong brine salinity gradient (a requirement for full-depth brine convection).…”
Section: Physical Imprints On Nutrient Incorporationsupporting
confidence: 55%
“…In spite of the observed biogeochemical zonation over the early‐melt period, high brine volume fractions (>5%; Figure g) indicate that brine convection should have connected, at least partially, all three zones and the underlying water column during our study [e.g., Carnat et al ., ; Zhou et al ., ]. Brine convection over the full ice column promotes solute (e.g., nutrients, DIC) exchange between the sea ice brine system and the surface ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Third, large refrozen vertical tubular drainage structure in the thin section pictures (Figure ), and inverted funnel‐shaped cavities at the bottom of a freshly taken ice core at station 2 (formed by turbulent microflows developing as outgoing brine encounter warmer inflowing water), both supportive of brine convection episodes [ Martin , ; Lewis et al ., ] were observed. These observations are consistent with recent time series studies of ice physical properties which showed that strong brine convection is likely to occur in warming ice at the end of the spring following the increase in brine volume fraction above the permeability threshold [ Carnat et al ., ; Jardon et al ., ; Zhou et al ., ]. Biological observations also supported brine convection.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were then allowed to melt at room temperature in sealed plastic containers, a process taking approximately 12 h. Bulk salinity was determined through conductivity by inserting the probe of a Thermo-Orion V R WP-84TPS conductimeter in each melted ice section (accuracy of 60.1&). Further details about basic physical measurements can be found in Carnat et al [2013].…”
Section: Physical Propertiesmentioning
confidence: 99%